PATHOGENETIC JUSTIFICATION OF DIFFERENTIAL THERAPY IN MENTAL DISORDERS WITH SOMATIC SYMPTOMS (PSS-BY DSM-5) - Rymsha, S.V.; Lukyanovych, I.L.; Rymsha, O.V. (World of Medicine and Biology, 2020)
The problem of prevalence and chronicity of psychogenic diseases becomes one of the most important in modern medicine in view of the economic losses associated with the compensation for this pathology treatment and its consequences. The purpose of the study was to formulate approaches for differential diagnosis and demonstrative use of medicines and psychotherapy for treatment of psychiatric disorders with somatic symptoms, taking into account pathogenic factors and their pathomorphosis. Conclusion was made that the evidence-based use in treatment of psychiatric disorders with somatic symptoms, taking into account pathogenic factors and their pathomorphosis, involves the predominant use of pregabalin as a universal neuromediator balance stabilizer in therapy of both anxiety disorders and other psychogenic disorders.